Do lean methodologies include ergonomic tools? - Maia, Laura Costa (2012)
This paper presents some methodologies for Lean implementation, highlighting which ergonomic tools are included in these methodologies. In order to achieve this, a review on ergonomic tools used to diagnostic work conditions was necessary. Being Lean Production, a well known work organizational model, widely implemented in all sort of industries and services companies in nowadays, it is important to include ergonomic tools for diagnose, evaluate and measure the workers conditions before and after the Lean implementation. Based on literature findings concern the existing Lean methodologies, it was possible to realize that none of the searched had these ergonomic tools implicit. In spite of this conclusion it was possible to identify the synergy between Ergonomic and Lean Production, encouraging the pursuit of a development a project that includes Ergonomic tools in a Lean methodology in order to assess the factors that impacts the worker ergonomic performance, before and after Lean implementation.